Examining the policy of mandatory premarital HIV screening programme for Muslims in Malaysia - Saidon, Rafeah; Kamaruddin, Zaleha; Arifin, Mahamad; Ibrahim, Norliah; Sahari, Noorul Huda (UPM Press, 2015)
One of the procedures introduced by the Government of Malaysia for Muslims before the solemnisation of their marriage is mandatory premarital HIV screening. The purpose of this procedure is to have an early detection of HIV infection which could reduce the possibility of sexually transmitted diseases to the offspring. This paper examines such a policy and reveals significant loopholes in the policy and its implementation. There are two types of methods employed in this study: library research and field research. Library research is used to examine the existing policy and its related issues such as social and medical issues. The finding is supported by field research in which semi-structured interviews were carried out with several respondents from the related institutions. The findings of the research revealed significant weaknesses in the current policy from both procedural and administrative aspects. These include a general lack of coordination in governing the screening programme, the absence of standard procedures in its implementation and the absence of guideline in maintaining confidentiality, among others.